Happiness indicator of MTUN staff's success factor - Ahmad, Muhamad Fazrulhelmi; Isa, Khairunesa; Palpanadan, Sarala @ Thulasi; Johar, Siti Sarawati; Jamin, J (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Feeling happy is fundamental to human experience in life. The interest in happiness has also extended to workplace experiences. There are some ways to know the factors that can contribute to the employee happiness. This paper tries to identify the success factors to determine happiness at the workplace among public university staff. A simple random sampling technique was executed as a methodology for this research. The data was collected using questionnaire from 535 university staff One of the Malaysian Technical University Network has been choose. The results showed that family and social factors have a high mean score to staff happiness while organizational factor has a low mean score to staff happiness. Therefore, this study tries to propose some approaches for organization to do in order to make staff happy in the workplace especially on the aspect of employee welfare.